Correlation of Microstructure and Properties of Cold Gas Sprayed INCONEL 718 Coatings - Vassen, R.; Fiebig, J.; Kalfhaus, T.; Gibmeier, J.; Kostka, A.; Schrüfer, Stefan (Journal of Thermal Spray Technology, 2020)
In the cold gas spray process, deposition of particles takes place through intensive plastic deformation upon impact in a solid state at temperatures well below their melting point. The high particle impact velocities and corresponding peening effects can lead to high compressive residual stresses in cold spray coatings. This can be advantageous with regard to mechanical properties as fatigue life and hence, cold spray is an ideal process for repair applications. In this study, INCONEL 718 particles were cold sprayed by using nitrogen as propellant gas. The deposited coatings with different thicknesses were characterized using electron microscopy techniques to study grain refinement and precipitates in the coating. In addition, depth-resolved residual stress measurements have been performed by the incremental hole drilling method. The residual stress depth profiles in the coatings indicate compressive residual stresses of several hundred MPa which are hardly influenced by the coating thickness. In addition, large compressive stress levels are found in surface-near regions of the substrate due to the grit blasting process. Furthermore, a post-heat treatment analysis was performed to investigate its influence on residual stresses and bonding strength. These findings are used to develop a consistent explanation of the dependence of strength values on thickness.
Created from Fastlane, Scopus look-up
Keywords: Cold gas spraying; Electron microscopy; INCONEL 718; Incremental hole drilling method; Residual stress